A mutual authentication scheme for establishing secure device-to-device communication sessions in the edge-enabled smart cities. (May 2021) - Zhang, Yanbin; Cheng, Ke; Khan, Fazlullah; Alturki, Ryan; Khan, Rahim; Rehman, Ateeq Ur
Abstract: Internet of Things (IoT) and edge-enabled networking infrastructures have been used to provide data processing capabilities at the edge rather than transferring it to the concerned cloud in the smart cities. However, security and privacy of both data and device C i are among common issues associated with the edge-enabled IoT networking paradigm. Numerous edge-enabled mechanisms have been presented in literature to resolve these issues, but device-to-device authentication (preferably in multi-hop enabled networking) to resolve the black-hole issue is not addressed yet. In this paper, a mutual authentication scheme, a hybrid of Medium Access Control (MAC) address and EAODV-enabled scheme, for establishing secure device-to-device communication sessions in IoT networks is presented to make edge-enabled smart cities safe and secure. Every device C i is bounded to register its Mac address with the concerned base station or edge module S j in an off-line phase to prevent entry of the intruder device(s) in the operational edge-enabled IoT network. Moreover, the initiation of a proper communication session with both device C i and edge or base station S j is subjected to the authentication process. Only those devices C i are allowed to initiate a communication session which are already registered in the off-line phase where entry of the intruder node(s) at any stage is not possible. Apart from it, a well-known encryption and decryption mechanism is used to guarantee a secure communication session. Simulation results have verified that the proposed mutual authentication scheme performance is better than existing schemes specifically in terms of processing and communication overheads.